1983
DOI: 10.1021/bi00291a020
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Overhauser effect as a tool for the complete assignment of nonexchangeable proton resonances in short deoxyribonucleic acid helixes

Abstract: A new strategy for the assignment of nonexchangeable proton resonances in oligonucleotide duplexes is presented and used to interpret the spectra of the oligonucleotide helix d(CpGpCpGpCpG) X d(CpGpCpGpCpG) in low salt (B form). This procedure is based on the use of sequential homodecoupling (1D) or COSY (2D) for the interconnection of the sugar resonances pertaining to the same residue and on the measurement of nuclear Overhauser effect (NOE) (1D or 2D) between critically located protons in order to establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…The first two-dimensional NMR experiments on doublehelical DNA were reported in 1982 by Feigon et al (1982) and independently by other groups (Frechet et al, 1983;Hare et al, 1983;Kaptein et al, 1983;Pardi et al, 1983a,b;Scheek et al, 1983). In this paper we have used two-dimensional nuclear Overhauser effect (2D NOE) spectroscopy to examine the structure of poly(dA-dT).…”
mentioning
confidence: 95%
“…The first two-dimensional NMR experiments on doublehelical DNA were reported in 1982 by Feigon et al (1982) and independently by other groups (Frechet et al, 1983;Hare et al, 1983;Kaptein et al, 1983;Pardi et al, 1983a,b;Scheek et al, 1983). In this paper we have used two-dimensional nuclear Overhauser effect (2D NOE) spectroscopy to examine the structure of poly(dA-dT).…”
mentioning
confidence: 95%
“…In addition, local conformational heterogeneity in the deoxyribose phosphate backbone has been most recently noted in the form of sequence-specific variations (Calladine, 1982;Dickerson, 1983;Dickerson & Drew, 1981) or as the result of drug (Saenger, 1984) or protein binding (Hochschild & Ptashne, 1986;Martin & Schleif, 1986;McClarin et al, 1986) to local regions of the DNA. While X-ray crystallography has provided much of our understanding of these DNA structural variations, increasingly, high-resolution NMR (particularly 'H/IH NOESY) has also begun to provide detailed three-dimensional structural information on duplex oligonucleotides (Broido et al, 1984;Feigon et al, 1983;Frechet et al, 1983;Hare et al, 1983;Kearns, 1984;Scheek et al, 1984;Schroeder et al, 1986Schroeder et al, , 1987van de Ven & Hilbers, 1988). Importantly, NMR experiments have suggested that the duplex conformation in solution (Assa-Munt & Kearns, 1984;Clore et al, 1985;Gorenstein et al, 1988;Nikonowicz et al, 1989;Patel et al, 1987;Rinkel et al, 1987) may not be identical with the static picture provided by X-ray diffraction in the crystal state.…”
mentioning
confidence: 99%
“…The development of sequence-specific, two-dimensional nuclear magnetic resonance (2D NMR) assignment methodologies (5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and higher-field spectrometers have made the study of modest size oligonucleotides (10-20 base pairs) possible. Two-dimensional NMR, combined with distance geometry (15)(16)(17) or restrained molecular mechanics/dynamics (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), is now capable of elucidating the fine structure of short DNA duplexes in solution. Unfortunately, evaluation of interproton distances from a 2D-NMR nuclear Overhauser effect spectroscopy (NOESY) experiment has relied on the so-called "two-spin approximation" (17,21).…”
Section: Introductionmentioning
confidence: 99%